Hipertensão arterial em mulheres idosas do programa Universidade Aberta à Terceira Idade da FCT/UNESP - Pansani, Aline Priscila [UNESP] (2006)
The arterial hypertension (HA) is considered a factor of primary risk with high prevalence in the population in general and that presents great importance in the context of the public health. Therefore, the objective of this work was to verify the prevalence of HA in women participants of the lectures offered by the program Open University to the Third Age developed by FCT/UNESP and to evaluate in the women with HA the following aspects: control of the blood pressure, time of medical diagnosis, accomplished treatment, signals and symptoms and presence of family history and stress. It had been analyzed 52 women who frequent the cited program, with average age of 66,19 ± 0,92 years, which had had its PA verified two times, with interval of 5 minutes between the measures, through indirect method. For analysis of the PA, the lesser value of the measures was used and its classification obeyed the criteria of IV Brazilian Directives of HA. Associated to the measures, a questionnaire that asked if the women possessed diagnosed HA, during how much time and which was the medication in use, which were the presented symptoms when PA rises, the use of nonpharmacologic treatment and the presence of hereditary succession and stress. Descriptive statistics was used for analysis of the data. Of analyzed women 59,62% had been classified as hypertensive, of which 12,90% did not possess a doctor diagnose. Of the aware hypertensive, 37,04% did not present controlled PA and 48,15% had the medical diagnosis done in the interval from 1 to 5 years; 66,67% presented symptom when of the increase of the PA, being the most common chronic headache (41,93%); 62,96% make use of nonpharmacologic treatment for HA, being physical activity the most used (50%), and 88,88% make use of pharmacological treatment. The hereditary succession was present in 67,74% of the .women and 12,90% had told stress intense. The results demonstrate that the studied population presents great prevalence of HA, what it strengthens the importance of works like this, objectifying the elaboration of prevention programs.